The Parkinson's plan : a new path to prevention and treatment - Dorsey, E. Ray; Okun, Michael S. (PublicAffairs, Hachette Book Group, 2025)
"In The Parkinson's Plan, two doctors on the cutting edge of Parkinson's research detail the steps necessary to prevent, slow, and treat this debilitating condition. They show readers how to prevent the disease through the food we eat, the water we drink, the air we breathe, and the lifestyles we live. They interview twenty-five of the world's top scientists, clinicians, and thought leaders in the Parkinson's field to build a plan for prevention and treatment. The Parkinson's Plan presents a clear road map with the strategies and tactics necessary to create a world where the disease is increasingly rare and the treatments are more successful"-- Provided by publisher.